2015
DOI: 10.3892/br.2015.433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diet on 1,2-dimethylhydrazine-induced aberrant crypt foci and colorectal tumours in rats

Abstract: Abstract. Obesity is one of the leading causes of numerous types of cancer. The present study investigated the impact of a high-fat diet on 1,2-dimethylhydrazine (DMH)-induced colorectal cancer (CRC) in F344 rats. A total of 16 male F344 rats aged 4 weeks were randomly divided into two groups (8 rats/group). Rats in group A were fed a basal diet with a moderate fat (MF) content, while rats in group B were fed a high-fat diet. Upon reaching 5 weeks of age, the rats were injected subcutaneously with DMH (20 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
2
3
0
1
Order By: Relevance
“…It was proven that increasing numbers of ACF appearing in the colon results in an increased risk of colon cancer [25]. The present study showed that all djulis-treated groups had significant reductions in the total number of ACF, and the high-dose djulis-treated group showed much-stronger inhibitory effects than did the low-dose djulis-treated group.…”
Section: Discussionsupporting
confidence: 54%
“…It was proven that increasing numbers of ACF appearing in the colon results in an increased risk of colon cancer [25]. The present study showed that all djulis-treated groups had significant reductions in the total number of ACF, and the high-dose djulis-treated group showed much-stronger inhibitory effects than did the low-dose djulis-treated group.…”
Section: Discussionsupporting
confidence: 54%
“…Diet rich in red meat and fats and low in fibers play a crucial role in the development of CRC [31]. HFD is thought to induce CRC through chronic inflammation, metabolic changes, and interference with cell cycle progression [32][33][34]. Therefore, in the current study, HFD was added to DMH to induce and accelerate CRC development and resemble human diet.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, a body of evidence indicated that the western diet habit (with higher total energy intake and red-meat intake) was a high risk of development of colorectal polyps in both number and size, as well as the left-sided advanced serrated lesions. [ 44 45 46 47 ] Further investigation is needed to find the exact reason for the lower prevalence of colorectal serrated polyps and different distribution of subtypes.…”
Section: Discussionmentioning
confidence: 99%